Interfacial engineering with NiOx nanofibers as hole transport layer for carbon-based perovskite solar cells. (December 2021) - Vijayaraghavan, S.N.; Wall, Jacob; Menon, Harigovind G.; Duan, Xiaomeng; Guo, Liping; Amin, Al; Han, Xiao; Kong, Lingyan; Zheng, Yufeng; Li, Lin; Yan, Feng
Highlights: Electrospun NiOx nanofibers as HTL for perovskite solar cells. Low-cost carbon electrode for the perovskite solar cells. Carbon-based perovskite with NiOx nanofibers as hole transport layer achieves a power conversion efficiency of ∼13.73%. The interface between carbon and perovskite was improved through the introduction of NiOx nanofibers. Abstract: Although perovskite solar cells (PSCs) have made revolutionary progress in terms of power conversion efficiency (PCE), to achieve long-term stability and low-cost device manufacturing for commercialization of the devices, selection of proper hole transport layer (HTL) and affordable back contact are still crucial to realize the upscale manufacturing. However, the carbon-based perovskite still faces great challenges to further improve the device performance due to the low quality of the carbon/perovskite interface. Inorganic NiOx is a superior HTL candidate due to its favorable energy band alignment, superior chemical stability, high hole mobility, and low-cost manufacturing. To address the poor interface quality of the carbon-based PSCs, we report electrospun NiOx fibers as an effective HTL, resulting in highly efficient device performance of PCEs up to 13.73% when deployed in our carbon-based PSCs. NiOx has been introduced as an interfacial layer between the perovskite and the carbon counter electrode to study its impact on interfacial modification and device performance.